2019
DOI: 10.1097/brs.0000000000002911
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Short-term Outcomes After Lumbar Fusion Between an Orthopedic Specialty Hospital and Tertiary Referral Center

Abstract: Study Design. A retrospective review of all elective single-level lumbar fusions performed at a single orthopedic specialty hospital (OSH) and tertiary referral center (TRC). Objective. This study compared the perioperative outcomes for lumbar fusion procedures performed at an OSH and TRC. Summary of Background Data. The role of an OSH for lumbar fusion procedures has not been defined. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(39 citation statements)
references
References 27 publications
1
38
0
Order By: Relevance
“…Although discharge destination was not directly studied in this cohort, previous studies have shown that patients undergoing surgery at OSHs have a higher proportion of home discharge compared with tertiary care centers, thus avoiding further care costs. 6,25 It is possible that our study may be underpowered to detect a statistically significant difference for this particular reimbursement metric.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although discharge destination was not directly studied in this cohort, previous studies have shown that patients undergoing surgery at OSHs have a higher proportion of home discharge compared with tertiary care centers, thus avoiding further care costs. 6,25 It is possible that our study may be underpowered to detect a statistically significant difference for this particular reimbursement metric.…”
Section: Discussionmentioning
confidence: 99%
“…5 The average length of stay (LOS) has been shown to be 30% shorter among lumbar fusion patients at OSHs compared to patients undergoing surgery at academic medical centers. 6 Additionally, despite similar demographics and comorbidity indices, patients are more likely to be discharged to home rather than to rehabilitation facilities, which lowers the overall financial burden on the health system and decreases the rate of facility-associated complications. 6,7 Lastly, tertiary referral centers are associated with significantly higher overhead costs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A study by Krietz, et al 2019, compared patients receiving a lumbar fusion in a orthopedic specialty hospital versus a tertiary referral center. The specialty hospital has statistically significant lower operative time, total operating room time, and length of stay when compared a tertiary referral center [15]. Specialty Hospitals brings numerous benefits directly to the patients and their families.…”
Section: Methodsmentioning
confidence: 99%
“…Lundgren et al found no difference in readmission scores or complication scores, following THA and TKA, between physician-owned OSHs and acute-care hospitals 26 . The following 6 studies took place at the same institution and potentially showed results from the same hospitals 14,15,18,[22][23][24] . Padegimas et al reported no difference, following THA, in 90-day readmission rates between an OSH (0.6%) and a general hospital (1.5%) or reoperation rates between an OSH (0.9%) and a general hospital (1.2%).…”
Section: Operative Time and Length Of Staymentioning
confidence: 99%